2009
DOI: 10.1143/jjap.48.03a050
|View full text |Cite
|
Sign up to set email alerts
|

Layer Stack Design of High Density Read-Only-Memory Discs for Near-Field Systems using a Solid Immersion Lens

Abstract: For high numerical aperture (NA) near-field systems using a solid immersion lens, layer stack types of first-surface read-only-memory (ROM) discs have been investigated. Complicated interactions of high-NA incident and diffracted waves with surface waves occur in multilayer-stacked subwavelength structures on the discs. Therefore, vector diffraction simulation in consideration of these effects is indispensable for the optimization of the disc structures. We used rigorous coupled wave analysis to numerically ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It can exhibit a large capacity and a highdata transfer rate towards recording next-generation ultrahigh-definition television [i.e., Super Hi-Vision (SHV), 7320 Â 4320 pixels] video signals 17,18) for home-use. Fourfold higher density recording using NFR optical disks with 1.2-mm-thick disks has been reported, 12,14) and studies of larger capacity using multilayer recording using NFR have been reported. 15,16) If the NFR media can realize 250-Mbpsclass high-speed recording and two-or three-layer recording, the SHV optical media, which has more than two hours recording ability would be able to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It can exhibit a large capacity and a highdata transfer rate towards recording next-generation ultrahigh-definition television [i.e., Super Hi-Vision (SHV), 7320 Â 4320 pixels] video signals 17,18) for home-use. Fourfold higher density recording using NFR optical disks with 1.2-mm-thick disks has been reported, 12,14) and studies of larger capacity using multilayer recording using NFR have been reported. 15,16) If the NFR media can realize 250-Mbpsclass high-speed recording and two-or three-layer recording, the SHV optical media, which has more than two hours recording ability would be able to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…These days, many impressive results of technical candidates for the next-generation optical discs have been reported in this field. The technical candidates include volumetric storage technology, [1][2][3][4][5][6] near-field technology, [7][8][9][10][11][12][13] and multilayer technology, [14][15][16][17][18][19][20] which is a volumetric storage technology. Among them, multilayer technology has a lot of advantages such as storage capacity, backward compatibility, and system practicability, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A near-field optical recording (NFR) system using a solid immersion lens (SIL) 1) has a fourfold higher recording density than the Blu-ray disc system. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some studies have shown the realization of a large recording capacity using multilayer recording techniques for optical disks, [17][18][19][20][21] but the data transfer rate is limited. The NFR system is expected to realize not only a large capacity but also a high data transfer rate because its numerical aperture (NA) is more than two times higher and the optical beam spot can be less than half the diameter of current Blu-ray optical systems.…”
Section: Introductionmentioning
confidence: 99%